Ablation of CD11chi dendritic cells exacerbates Japanese encephalitis by regulating blood-brain barrier permeability and altering tight junction/adhesion molecules. (October 2016) - Kim, Jin Hyoung; Hossain, Ferdaus Mohd Altaf; Patil, Ajit Mahadev; Choi, Jin Young; Kim, Seong Bum; Uyangaa, Erdenebelig; Park, Sang-Youel; Lee, John-Hwa; Kim, Bumseok; Kim, Koanhoi; Eo, Seong Kug
Graphical abstract: Highlights: CD11c hi DC ablation resulted in markedly increased susceptibility to JE progression along with highly increased neuro-invasion of JEV. Exacerbation of JE progression in CD11c hi DC-ablated hosts was coupled to enhanced BBB permeability. CD11c hi DC ablation reduced the expression of tight junction and adhesion molecules (claudin-5, ZO-1, occluding, JAMs). CD11c hi DC ablation provide subsidiary impact on BBB integrity and tight junction/adhesion molecules, thereby leading to exacerbated JE progression. Abstract: Japanese encephalitis (JE), characterized by extensive neuroinflammation following infection with neurotropic JE virus (JEV), is becoming a leading cause of viral encephalitis due to rapid changes in climate and demography. The blood-brain barrier (BBB) plays an important role in restricting neuroinvasion of peripheral leukocytes and virus, thereby regulating the progression of viral encephalitis. In this study, we explored the role of CD11c hi dendritic cells (DCs) in regulating BBB integrity and JE progression using a conditional depletion model of CD11c hi DCs. Transient ablation of CD11c hi DCs resulted in markedly increased susceptibility to JE progression along with highly increased neuro-invasion of JEV. In addition, exacerbated JE progression in CD11c hi DC-ablated hosts was closely associated with increased expression of proinflammatory cytokines (IFN-β, IL-6, and TNF-α) and CC chemokines (CCL2, CCL3, CXCL2) in the brain. Moreover, our results revealed that the exacerbation of JE progression in CD11c hi DC-ablated hosts was correlated with enhanced BBB permeability and reduced expression of tight junction and adhesion molecules (claudin-5, ZO-1, occluding, JAMs). Ultimately, our data conclude that the ablation of CD11c hi DCs provided a subsidiary impact on BBB integrity and the expression of tight junction/adhesion molecules, thereby leading to exacerbated JE progression. These findings provide insight into the secondary role of CD11c hi DCs in JE progression through regulation of BBB integrity and the expression of tight junction/adhesion molecules.